ANALISIS SISTEM VENTILASI TAMBANG UNTUK KEBUTUHAN OPERASIONAL PENAMBANGAN PADA TAMBANG BAWAH TANAH OMBILIN 1 (SAWAHLUWUNG) PT. BUKIT ASAM – UPO - Ari Febrianda Bafnis; Bambang Heriyadi; Sumarya Sumarya (Departemen Teknik Pertambangan FT UNP, 2014)
PT. Bukit Asam - UPO is a coal underground mining company that conducted mining in the areas Ombilin I (Sawahluwung), Ombilin II (Waringin-Sugar) and Ombilin III (Sigalut).On the mining production in the underground mining, PT. Bukit Asam-UPO used exhaust ventilation system with the quantity of air out is 35.56 m3/s, whereas the intake air quantity is 35.07 m3/s through the three inlets, they are Adit Sawahluwung is 25.28 m3/s, Lurah Sapan I is 7.14 m3/s and Lurah Sapan II is 2.65 m3/s. The amount of air entering and the air out there is a difference of 0.49 m3/s which may be caused by air leaks at Mine Vein.The air quantity available on the front J6C is 4.02 m3/s, front J9C is 3.17 m3/s, front J11C is 2.94 m3/s and front Dosco is 3.15 m3/s. While the minimum air quantity to be supplied is for front J6C is 2.17 m3/s, front J9C is 2.50 m3/s, front J11C is 2.50 m3/s and front Dosco is 2.17 m3/s.In terms of air quality in underground mines Sawahluwung already on the threshold value has been determined, for CH4 <1%, CO2 <0.5%, CO <0.0005%, O2> 19%, the effective temperature (Te) at 21 0 C – 32 0 C and the relative humidity (RH) 65% - 95%. Keywords: Ventilation Air Requirements, Quantity and quality of the mine air